Characteristics and reference values for cardiopulmonary exercise testing in the adult Chinese population – The Xiangya hospital exercise testing project (the X-ET project). (1st June 2021) - Dun, Yaoshan; Olson, Thomas P.; Li, Cui; Qiu, Ling; Fu, Siqian; Cao, Zeng; Ripley-Gonzalez, Jeffrey W.; You, Baiyang; Li, Qiuxia; Deng, Lihua; Li, Qingfang; Liu, Suixin
Abstract: Background: Reference values of cardiopulmonary exercise testing (CPX) vary with race/ethnicity. Chinese Americans are the fastest-growing racial/ethnic group in the United States. However, there is limited information about the reference values of cardiopulmonary exercise testing (CPX) variables in the Chinese population. Methods: As part of the Xiangya Hospital Exercise Testing project (the X-ET project), this cross-sectional study screened 20, 696 consecutive CPXs performed by 17, 802 unique individuals at Xiangya Hospital of Central South University, China, from January 1, 2002, to December 31, 2019. A total of 964 unique healthy adults/tests (42% female) aged 49 ± 12 who completed a maximal ramp incremental CPX with cycle ergometry were included in this study. The reference values of primary CPX variables were expressed as the lower limit or upper limit of normal. Stepwise linear regression was used to fit the equations of key CPX variables. Predictive accuracy analysis for the equations with a comparison between present and previous studies were performed. Results: Peak oxygen consumption ( V ̇ O2 ), carbon dioxide production, ventilation/min, work rate, and V ̇ O2 at the anaerobic threshold were regressed on age, height, weight, and sex. These predictive equations showed good in- and out-sample predictive accuracy. Comparison with prior research revealed that prediction equations of peak V ̇ O2 resultant from studies in which populations were entirely or primarily Caucasian had overestimated our subjects' actual values. Conclusion: The reference values and predicted equations of CPX variables in this study may provide a more appropriate framework to interpret the response to maximal ramp incremental cycle ergometry in the Chinese adult population. Highlights: The reference values of key CPX variables in Chinese population are described. Comparisons were made between present and past predictive CPX variable equations. Our equations of key CPX variables fitted well to the Chinese population. Results may provide an appropriate frame to interpret CPX in Chinese population.